Insights Into Dendritic Cells in Cancer Immunotherapy: From Bench to Clinical Applications - Salah, Ahmed; Wang, Hao; Li, Yanqin; Ji, Meng; Ou, Wen-Bin; Qi, Nianmin; Wu, Yuehong (Frontiers in Cell and Developmental Biology, 2021)
Dendritic cells (DCs) are efficient antigen-presenting cells (APCs) and potent activators of naïve T cells. Therefore, they act as a connective ring between innate and adaptive immunity. DC subsets are heterogeneous in their ontogeny and functions. They have proven to potentially take up and process tumor-associated antigens (TAAs). In this regard, researchers have developed strategies such as genetically engineered or TAA-pulsed DC vaccines; these manipulated DCs have shown significant outcomes in clinical and preclinical models. Here, we review DC classification and address how DCs are skewed into an immunosuppressive phenotype in cancer patients. Additionally, we present the advancements in DCs as a platform for cancer immunotherapy, emphasizing the technologies used for in vivo targeting of endogenous DCs, ex vivo generated vaccines from peripheral blood monocytes, and induced pluripotent stem cell-derived DCs (iPSC-DCs) to boost antitumoral immunity.